Küreselleşme Sürecinde Hemşehri Dernekleri - Akaslan, Mehmet Emin (My University, 2003)
Soyadı : Mehmet Emin Akaslan lahiyat Felsefe ve Din Bilimleri Yar. Doç. Dr. Ali Coşkun Tez Türü ve Tarihi : Yüksek Lisans reselleşme, Hemşehri Dernekleri

KÜRESELLEŞME SÜRECİNDE HEMŞEHRİ DERNEKLERİ Küreselleşme sürecinde dünya bir yandan köy haline gelirken öte yandan her türlü farklılık ve yerellik de meşrulaştırılmaktadır. Bu durum bir yandan dünyayı bir örnekleştirirken öte yandan dünya çoğulluklar içinde kaybolmaktadır. Sanayi devrimiyle beraber yaşanan kentleşme süreciyle, taşradan büyük kentlere gelen insanlar, kalabalıklar içinde kaybolmamak için bir araya gelmişler ve zamanla bu hemşehrilik ilişkisini, hemşehri dernekleri kurarak formel hale getirmişlerdir. Hemşehri derneklerinde yapılan faaliyetler hemşehrileri bir araya getirdiği gibi, yöresel kültürlerini, geleneklerini, göreneklerini koruyup yaşatmalarına da vesile olmaktadır. Geleneksel kültürün ana ekseninin din olması faaliyetlere de yansımaktadır. Dinin daha çok nesnel boyutu, yani toplumda iyice yerleşmiş ve bir nevi kültürleşmiş kısımları bu faaliyetler içinde görülmektedir. Bu şekilde hemşehri dernekleri kente uyumu kolaylaştırabilmekte, hitap ettiği kitlenin dini hayatını da dengeleyici bir rol oynayabilecek özelliklere sahip olduğunu göstermektedir. Name and Surname : Mehmet Emin Akaslan Field : Divinity Programme : Philosophy and Religion Sciences Supervisor : Assistant Professor Ali Coşkun Degree Awarded and Date : Master - August 2003 Globalisation, Fellow Countrymanship Societies ABSTRACT FELLOW COUNTRYMANSHİP SOCİETİES İN THE PROCESS OF GLOBALİSATİON In the process of globalisation, while the world becomes a village, on the other hand, every type of difference and locality is being legitimated. Though this situation makes the world uniformed with regard to adopting the dominant culture, it also causes the world to be lost in pluralities. One of the most predominant kind of this pluralities in developing countries is in the form of fellow countrymanship. People who came from same rural areas to cities in the process of urbanisation, which is occurred after Industrial Revolution, got together and in the course of time, they make this relationship more formal by founding fellow countrymanship societies. The activities which are held in these societies, beside providing the opportunity of getting together fellow countrymen, facilitate them to retain and maintain their local cultures, traditions and customs. The fact that the main axis of traditional culture is religion reflects to the activities of those societies. Especially the objective dimension of religion, which took roots among the people and which is, say, culturized, can be seen in the activities of these societies. Therefore, fellow countrymanship societies both facilitate the adaptation process to the city life and prove their capacity in balancing the religious life of their members
Keywords: Dernekler; Küreselleşme